CRISPR/Cas13-Mediated Inhibition of EBNA1 for Suppression of Epstein–Barr Virus Transcripts and DNA Load in Nasopharyngeal Carcinoma Cells - Lin Lin; Wai-Yin Lui; Chon Phin Ong; Mabel Yin-Chun Yau; Dong-Yan Jin; Kit-San Yuen (Viruses, 2025)
Epstein–Barr virus (EBV), a double-stranded DNA virus, is implicated in nasopharyngeal carcinoma (NPC), with particularly high incidence in regions such as southern China and Hong Kong. Although NPC is typically treated with radio- and chemotherapy, outcomes remain poor for advanced-stage diagnoses, highlighting the need for targeted therapies. This study explores the potential of CRISPR/CRISPR-associated protein 13 (Cas13) technology to target essential EBV RNA in NPC cells. Previous research demonstrated that CRISPR/Cas9 could partially reduce EBV load, but suppression was incomplete. Here, the combination of CRISPR/Cas13 with CRISPR/Cas9 shows enhanced viral clearance. Long-term EBNA1 suppression via CRISPR/Cas13 reduced the EBV genome, improved CRISPR/Cas9 effectiveness, and identified suitable AAV serotypes for delivery. Furthermore, cotreatment increased NPC cell sensitivity to 5-fluorouracil and cisplatin. These findings underscore the potential of CRISPR/Cas13 as an anti-EBV therapeutic approach, effectively targeting latent EBV transcripts and complementing existing treatments. The study suggests a promising new direction for developing anti-EBV strategies, potentially benefiting therapies for NPC and other EBV-associated malignancies.